2023
DOI: 10.1371/journal.pone.0280553
|View full text |Cite
|
Sign up to set email alerts
|

Delpinium uncinatum mediated green synthesis of AgNPs and its antioxidant, enzyme inhibitory, cytotoxic and antimicrobial potentials

Abstract: Green synthesis of nanoparticles is becoming a method of choice for biological research due to its environmentally benign outcomes, stability and ease of synthesis. In this study, silver nanoparticles (AgNPs) were synthesized using stem (S-AgNPs), root (R-AgNPs) and mixture of stem and root (RS-AgNPs) of Delphinium uncinatum. The synthesized nanoparticles were characterized by standardized techniques and evaluated for their antioxidant, enzyme inhibition, cytotoxic and antimicrobial potentials. The AgNPs exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
3
2
0
Order By: Relevance
“…Silver nanoparticles can increase oxidative stress through the reduction of glutathione (GSH) and superoxide dismutase (SOD) and enlargement of lipid peroxidation for reaching the ultimate objective of apoptosis by intensifying caspase‐3 activity and DNA fragmentation. Ag nanoparticles and unbounded Ag ions have a tendency for forming interactions with thiol groups on the surface of GSH as well as reduced proteins similar to SOD, thioredoxin, and thioredoxin peroxidase [45] . Being comparable to the data of other reports, the present study denoted an extension in the rate of toxicity after amplifying the exerted concentration.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Silver nanoparticles can increase oxidative stress through the reduction of glutathione (GSH) and superoxide dismutase (SOD) and enlargement of lipid peroxidation for reaching the ultimate objective of apoptosis by intensifying caspase‐3 activity and DNA fragmentation. Ag nanoparticles and unbounded Ag ions have a tendency for forming interactions with thiol groups on the surface of GSH as well as reduced proteins similar to SOD, thioredoxin, and thioredoxin peroxidase [45] . Being comparable to the data of other reports, the present study denoted an extension in the rate of toxicity after amplifying the exerted concentration.…”
Section: Resultssupporting
confidence: 89%
“…Ag nanoparticles and unbounded Ag ions have a tendency for forming interactions with thiol groups on the surface of GSH as well as reduced proteins similar to SOD, thioredoxin, and thioredoxin peroxidase. [45] Being comparable to the data of other reports, the present study denoted an extension in the rate of toxicity after amplifying the exerted concentration. Nonetheless, the performance of rigorous assessments can aid to achieve a sufficient conception on the true nature of the cytotoxicity of the synthesized nanoparticles.…”
Section: Cytotoxic Performancesupporting
confidence: 92%
“…For this reason, in recent increase in thermal resistance. Similar results have been demonstrated in many previous studies [56,57].…”
Section: Lpo Inhibitory Activitysupporting
confidence: 93%
“…NPs obtained using a mixture of plant stem and root were characterized by the highest antifungal activity and significant inhibition of Aspergillus flavus. [118] In turn, Scroccarello et al tested the antifungal activity against Aspergillus niger of Ag NPs synthesized using various phenolic compounds, it turned out that all the compounds obtained had an inhibitory effect on mycelial growth, and the most effective were catechin-terminated NPs. [119] Research done by İpek et al confirmed the antipathogenic properties of Au NPs, in which an aqueous extract from the red skin of Allium cepa was used in the synthesis.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%